Evaluation of the retinal hemodynamics in patients with primary open angle glaucoma and differing nocturnal blood pressure profiles - Yusof @ Alias, Firdaus; Cheng, Richard; Espahbodi, Nadia; Khuu, Lee-Anne; M Buys, Yvonne; Trope, Graham; Hudson, Christopher; Flanagan, John G (Association for Research in Vision and Ophthalmology, 2014)
Purpose: To evaluate the retinal hemodynamic response to normoxic hypercapnia among patients with primary open angle glaucoma (POAG) and differing nocturnal blood pressure (NBP) profiles, using Doppler spectral-domain optical coherence tomography (SD-OCT).